The role of new information and communication technologies in modern education - Daineko, Ye.A.; Ipalakova, M.T.; Tsoy, D.D.; Seitnur, A.M. (Recent Contributions to Physics, 2021)
The technological advances of the last 15 years have made a huge contribution to modern society, transforming education and training. Computers and the Internet allow teachers and students to work, learn, and receive information in ways that were once unthinkable. One of the latest and yet most exciting technological developments in education is the use of virtual reality (VR) and augmented reality (AR) to enhance learning opportunities. Virtual reality and augmented reality allow users to interact with computer environments, real or imagined. VR also allows users to receive visual, auditory, tactile, smell, and taste inputs in three-dimensional space.As a result, the authors implemented a virtual laboratory with the possibility of conducting a virtual experiment, which includes practical and theoretical tasks in high school physics, as well as a set of animations. When developing the virtual electronic laboratory, agile software development methodologies, computer modeling methods, and object-oriented programming were used. As a virtual reality device, the Leap Motion motion controller was chosen, designed to track the movements of hands and fingers in space and used for human-computer interaction. The article provides UML activity diagrams for working and interacting with the application. The cross-platform Unity 3D environment, which implements the WORA (write once, run anywhere) principle, was chosen as the development platform. Thanks to this principle, a once-written application can be built for personal computers, mobile devices, mixed reality helmets, and many other platforms. The application functionality was written in the C# programming language. Graphic models were created using Substance Painter. The developed application can be used by students of senior classes of secondary and specialized schools, students of technical majors of higher educational institutions, as well as any interested users.
Keywords: virtual laboratory; augmented reality; virtual reality; 3D modeling; Unity3D; С# (CSharp)